(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article examines international experiences in implementing innovation processes within primary education systems. It explores education policies, pedagogical technologies, digitalization practices, and teacher professional development programs adopted by various countries. The study highlights the role of innovative approaches in improving students’ competencies and enhancing the quality of education. The findings provide insights into advanced practices that can be adapted for the primary education system of Uzbekistan.